Waiting longer, feeling fatter: Effects of response delay on tactile distance estimation and confidence in females with anorexia nervosa. Issue 3 (28th November 2021) - Engel, Manja M.; Gadsby, Stephen; Corcoran, Andrew W.; Keizer, Anouk; Dijkerman, H. Chris; Hohwy, Jakob
Abstract: Background: Research suggests that patients with anorexia nervosa (AN) exhibit differences in the perceptual processing of their own bodies. However, some researchers suggest that these differences are better explained with reference to non‐perceptual factors, such as demand characteristics or emotional responses to the task. In this study, we investigated whether overestimation of tactile distances in participants with AN results from differences in tactile processing or non‐perceptual factors, by measuring the role of allowed response time in an adapted version of the tactile distance estimation task (TDE‐D). We further investigated the relationship between allowed response time and participants' confidence in their tactile judgments. Method: Our sample consisted of females: participants with AN ( n = 30), recovered (REC) participants ( n = 29) and healthy controls (HC) ( n = 31). Participants were asked to estimate tactile distances presented on the skin of either a salient (abdomen) or non‐salient (arm) body part, either directly after stimulus presentation (direct condition) or after a 5 s delay (delayed condition). Confidence of estimation accuracy was measured after each response. Results: Results showed that allowing AN and REC more time to respond caused them to estimate tactile distances as larger. Additionally, participants with AN became less confident when given more time to respond. Conclusions: These results suggest that non‐perceptual influences cause participants with AN to increase their estimates of tactile distances and become less certain of these estimates. We speculate that previous findings—where participants with AN estimate tactile distances as larger than HC—may be due to non‐perceptual differences. Abstract :